Revolutionary violence from Maurice Merleau-Ponty to Étienne Balibar - Beas Marín, Pablo; Moreno Pestaña, José Luis (Las Torres de Lucca. International Journal of Political Philosophy, 2026)
This article explores the relationship between Étienne Balibar and Merleau-Ponty regarding the convertibility of revolutionary violence. Both authors consider violence to be an irreducible element of human existence and, through different intellectual itineraries, consider the risks for emancipatory politics that the recourse to violence, which is always unpredictable, may involve. The figure of Hegelian conversion is enriched in Balibar with a psychoanalytical perspective that allows him to raise the possibility of inconvertible violence. In Merleau-Ponty, for his part, violence is tragically bound up with contingency to arrive at similar conclusions. We consider that this is a philosophical dialogue that is surprisingly absent in the work on violence conducted by Balibar in the context of Violence et Civilité.